Aplicación de la teoría de las decisiones a las SIEFORES en México (Application of decision theory to SIEFORES in Mexico) - Banda Ortiz, Humberto; González García, Luis Miguel; Gómez Hernández, Denise (Facultad de Contaduría Pública y Administración U.A.N.L., 2012)
Abstract: There are different theories that try to explain the decision making process. These theories set out some possible decision scenarios. In this article we applied the decision theory to the different options offered by SIEFORES yields, in order to demonstrate performance and risk in some scenario. In this paper first at all we study decision theory, following we explain the SIEFORES system in Mexico. In the last part we apply decision making model to the SIEFORES.